Proposed interior design scheme of Yamaha Music Sdn. Bhd. retail at 2-1 kedai & 2- 2A Jalan Sultan Yussuf, 30000 Ipoh,Perak Darul Ridzuan / Mohamad Khairie Ridhwan Azmi - Azmi, Mohamad Khairie Ridhwan (Faculty of Architecture, Planning and Surveying, 2012)
This project is to propose Interior Design scheme of Yamaha Music Sdn. Bhd. retail at 2-1 Kedai& 2-2A Jalan Sultan Yussuf, 30000 Ipoh, Perak. The aim of the project is to provide a comfortable space with facilities and activities specifiedfor music at new retail branch. The retail and gallery goal is to give musician a foundation of understanding by broadening their knowledge of spatial design through the study of the plan and plan language. The objective of the project is to form a good design which has good flow traffic and allows easy access and also to expand client business which is a new branch at Ipoh, Perak. Moreover, it is also to help the musician to make a choice of instrument or percussion at Yamaha Music Sdn. Bhd. and also to overcome design issue that related to the concept of the interior design. The focus of the methodology of how the plan is presented developed and understood interior design Yamaha Music Sdn. Bhd. retail and gallery. The plan is what architects, interior designers use to move people through space, to organize space, and to place objects in space.The project chosen must have general issue and design issuerelated to them in order for it to be a visible project. The thing that has been discovered is that the retail and gallery is facing design problem such as the planning which leads to the traffic flow disorder in the building. This means like facade design,entrance,and customer flow in Yamaha Music Sdn. Bhd. retail and gallery.Only in Kuala Lumpur have Yamaha Music Sdn. Bhd. retail and gallery. In Ipoh,Perak there is no retailbut just have Yamaha Music shop.Function retail is to give a new product from Yamaha Music to introduce to all musicians.These issues will be solve by the designers design after analyzing all the detail needed before starting the design process. For this final project, I have proposed is the project proposed new the Yamaha Music Sdn. Bhd. retail and gallery for Yamaha Music (Malaysia) HQ at no 8. Jalan Perbandaran Kelana Jaya, 47301 Petaling Jaya,Selangor,Malaysia.The proposed new process of the project consists of the concept,image,planning, material and finishes. The concept I have choose for this project is ‘Soul of Rhythm’.Rhythm is mean as Rhythm (from Greek "any regular recurring motion, symmetry") may be generally defined as a "movement marked by the regulated succession of strong and weak elements, or of opposite or different conditions". This general meaning of regular recurrence or pattern in time may be applied to a wide variety of cyclical natural phenomena having a periodicity or frequency of anything from microseconds to millions of years.Melody is mean as a melody (from Greek “singing, chanting”), also tunes, voice, or line, is a linear succession of musical tones which is perceived as a single entity. It also is an exponential succession of musical tones which is perceived as two entities. In its most literal sense, a melody is a combination of pitch and rhythm, while more figuratively, the term has occasionally been extended to include successions of other musical elements such as tone color. It may be considered the foreground to the background accompaniment. A line or part need not be a foreground melody.So.this concept is very suitable for Yamaha Music to transform into retail.